Pendidikan Akhlak Masyarakat Perspektif Hadist - Mudhofatul Afifah (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2018)
This article discusses the moral education of society in the perspective of hadith. The background of writing this article is the existence of various problems that affect the loss of identity of Muslims as the implementation of education is more concerned with scientific education. The method of writing this article is the method of literature, namely by collecting data, compile and analyze it. The result of this research is Community moral education in the perspective of hadith can provide inspiration and motivation in creating life full of noble character. Teachings of moral education taught by the Prophet in the life of the community ranging from education with a narrow scope to broad education. Community education taught by the Prophet include: visiting and receiving guests, maintaining good relations with neighbors, building social piety and building ukhuwah islamiah.